Is depression associated with periodontal status in elderly? - Leonel Ramonnd Ferreira Viana; Consuelo Penha Castro; Hellen-Bry Wanderley Pereira; Adriana de Fátima Vasconcelos Pereira; Fernanda Ferreira Lopes (Universidade Estadual de Campinas, 2015)
Aim: To examine whether the depression is associated with periodontitis in elderly and to evaluate oral hygiene of these patients. Methods: One hundred and ninety one individuals aged 60 years or more were randomly selected. Periodontal examination was performed in full mouth by probing depth and clinical attachment loss in 6 sites for each tooth. The Simplified Oral Hygiene Index (OHI-S) per individual was also obtained. Depression was assessed by the Geriatric Depression Scale (GDS-15) to show how the elderly have been feeling during the last week. Results: Only SOHI was statistically significant (t = 4.7169, p<0.001), which better explains the variance in periodontal status. The variable GDS-15 revealed no significant values (t=0.3901, p=0.6971). Conclusions: There was no association between periodontitis and depression in elderly, but there was association between periodontitis and oral hygiene.